Antagonism of NativeTrichodermaspp. from the Peruvian Central Rainforest onPhytophthora capsiciand Effects on Capsicum annuum - Teves Anchivilca, Percy Ivan (2024)
The genus Trichoderma is primarily recognized for its role as a biocontrol agent against various plant pathogens. Among the actions exhibited by this genus is its activity against Phytophthora capsici (P.c.), the causal agent of crown rot, foliar blight, and fruit rot in pepper cultivation. This study evaluated the antagonistic activity of T. koningiopsis and T. lentiforme against P. capsici. These species, isolated from the Peruvian central rainforest, were previously identified through morphological and molecular methods. The research was conducted in two phases: 1) In the in vitro phase, the treatments included isolates of T. koningiopsis, T. lentiforme, and T. harzianum, each tested both individually and against P. capsici, along with a positive control (+P.c.); 2) For the in vivo phase a negative control (-P.c.) was included. The in vitro antagonism evaluation featured a dual plate confrontation assay between Trichoderma spp. and P. capsici on Potato Dextrose Agar (PDA) medium, wherein the percentage of radial growth inhibition (PRGI) and growth rate were assessed. In the greenhouse, bell pepper seedlings cv ‘Piquillo’ were inoculated with 20 mL of a Trichoderma spp. conidia suspension (108 spores/mL) at transplanting, 14, and 28 days after transplanting (dat).  P. capsici was inoculated at 28 dat near the base of the plant using three grains (0.27 g) of previously colonized wheat. The experiments followed a completely randomized design (CRD) with Tukey’s mean comparison test at a 0.05 significance level. The evaluated variables included plant height (cm), incidence (%), severity (%), fresh weight (g), and dry weight (g). The in vitro antagonism results showed that T. koningiopsis and T. lentiforme exhibited PRGI values of 38.08 % and 37.91 %, respectively, against P. capsici. In the greenhouse assay, the bell pepper plants co-inoculated with T. lentiforme and P. capsici exhibited higher values in plant height (21.11 cm), root length (11.02 cm), and fresh weight (1.4 g). Additionally, the degree of foliar and root severity in all treatments with Trichoderma spp. and P. capsici was lower (Grade 0 to Grade 2), unlike the treatment inoculated solely with the pathogen (Grade 3 to Grade 4). In conclusion, this study demonstrates the potential of T. koningiopsis and T. lentiforme as biocontrol agents against P. capsici in pepper crops.